Chronological Model of a Brazilian Holocene Shellmound (Sambaqui da Tarioba, Rio de Janeiro, Brazil). Issue 2 (2014) - Macario, K D; Souza, R C C L; Trindade, D C; Decco, J; Lima, T A; Aguilera, O A; Marques, A N; Alves, E Q; Oliveira, F M; Chanca, I S; Carvalho, C; Anjos, R M; et al.
Abstract : Since the beginning of the Holocene, hunter-gatherers have occupied the central-south Brazilian coast, as it was a very productive estuarine environment. Living as fishers and mollusk gatherers, they built prehistoric shellmounds, known as sambaqui, up to 30 m high, which can still be found today from the Espírito Santo (21°S) to Rio Grande do Sul (32°S) states, constituting an important testimony of paleodiversity and Brazilian prehistory. The chronology of the Sambaqui da Tarioba, situated in Rio das Ostras, Rio de Janeiro, is discussed herein. Selected well-preserved shells of Iphigenia brasiliana and charcoal from fireplaces in sequential layers were used for radiocarbon dating analysis. Based on a statistical model developed using OxCal software, the results indicate that the settlement occupation begun most probably around 3800 cal BP and lasted for up to 5 centuries.